Direct Current Electric Stimulation in Implant Osseointegration: An Experimental Animal Study With Sheep - (:unkn) unknown (ALLEN PRESS INC, 2013)
In an effort to obtain a high-quality bone-implant interface, several methods involving alteration of surface morphological, physicochemical, and biochemical properties are being investigated. The aim of our study was to increase the osseointegration rate and quality and decrease the waiting period of dental implants before loading by using a microelectric implant stimulator device. It imitates rnicroelectrical signals, which occur in bone fractures described in terms of piezoelectric theory. A single dental implant (Zimmer Dental), 3.7 mm in diameter, was inserted into the tibia of sheep bilaterally. Twenty-four dental implants were inserted into 12 sheep. Implant on the tibia of each sheep was stimulated with 7.5 mu A direct current (DC), while the other side did not receive any stimulation and served as a control. Animals were sacrificed 1, 2, and 3 months after implantation. Bone segments with implants were processed with unclassified method. The determination of new bone formation and osseointegration around the dental implants was investigated by means of undecalcified method, histomorphologically. No statistically significant difference in bone-to-implant contact (BIC) ratio, osteoblastic activity, and new bone formation was found between the stimulation group and the control group at the late phase of healing (4, 8, and 12 weeks). No evidence was found that electric stimulation with implanted 7.5 mu A DC is effective at late phase implant osseointegration on a sheep experimental model.
Keywords: bone formation; electric stimulation; dental implant; osseointegration; ELECTROMAGNETIC-FIELDS; DENTAL IMPLANTS; BONE-FORMATION; DELAYED UNION; DIFFERENTIATION; OSTEOGENESIS; NONUNION; TISSUES